Albatrosses develop attraction to fishing vessels during immaturity but avoid them at old age. Issue 1990 (11th January 2023) - Weimerskirch, Henri; Corbeau, Alexandre; Pajot, Adrien; Patrick, Samantha C.; Collet, Julien
Abstract : Animals have to develop novel behaviours to adapt to anthropogenic activities or environmental changes. Fishing vessels constitute a recent feature that attracts albatrosses in large numbers. While they provide a valuable food source through offal and bait, they cause mortalities through bycatch, such that selection on vessel attraction will depend on the cost–benefit balance. We examine whether attraction to fishing and other vessels changes through the lifetime of great albatrosses, and show that attraction differed between age classes, sexes and personality. Juveniles encountered fewer vessels than adults, but also showed a lower attraction to vessels when encountered. Attraction rates, especially for fishing vessels, increased through immaturity to peak during adulthood, decreasing with old age. Shy females had lower attraction to vessels and shy males remained at vessels longer, suggesting that bolder individuals may outcompete shyer ones, with positive consequences for mass gain. These results suggest that attraction to vessels is a learned process, leading to an increase with age, and is not the result of preferential attraction to new objects by juveniles. Overall, our findings have important conservation implications as a result of potential strong differential selection on the risk of bycatch for age classes, personality types, populations and species.